Crystal Formation by a Ribonucleic Acid Polymerase Mutant of Bacillus subtilis - Santo, Leatrice Y. (1973)
A crystalline inclusion has been observed in a ribonucleic acid polymerase mutant of Bacillus subtilis which is conditionally temperature sensitive only during sporulation. The crystal is formed at the permissive temperature in 1 to 2% of the sporulating (stage III–IV) cells; about 85% of the cells sporulate normally, while the cells with crystals do not sporulate. The wild type does not form crystals at either the permissive (30 C) or the nonpermissive (47 C) temperatures. The crystal may result from altered transcription during sporulation at 30 C.